Soft, stretchable, high power density electronic skin-based biofuel cells for scavenging energy from human sweat. Issue 7 (22nd June 2017) - Bandodkar, Amay J.; You, Jung-Min; Kim, Nam-Heon; Gu, Yue; Kumar, Rajan; Mohan, A. M. Vinu; Kurniawan, Jonas; Imani, Somayeh; Nakagawa, Tatsuo; Parish, Brianna; Parthasarathy, Mukunth; Mercier, Patrick P.; et al.
Abstract : A soft, stretchable wearable biofuel cell producing ∼1 mW power from sweat is presented. Abstract : This article describes the fabrication, characterization, and real-life application of a soft, stretchable electronic-skin-based biofuel cell (E-BFC) that exhibits an open circuit voltage of 0.5 V and a power density of nearly 1.2 mW cm −2 at 0.2 V, representing the highest power density recorded by a wearable biofuel cell to date. High power density is achieved via a unique combination of lithographically-patterned stretchable electronic framework together with screen-printed, densely-packed three-dimensional carbon-nanotube-based bioanode and cathode array arranged in a stretchable "island-bridge" configuration. The E-BFC maintains its performance even under repeated strains of 50%, and is stable for two days. When applied directly to the skin of human subjects, the E-BFC generates ∼1 mW during exercise. The E-BFC is able to power conventional electronic devices, such as a light emitting diode and a Bluetooth Low Energy (BLE) radio. This is the first example of powering a BLE radio by a wearable biofuel cell. Successful generation of high power density under practical conditions and powering of conventional energy-intense electronic devices represents a major step forward in the field of soft, stretchable, wearable energy harvesting devices.